Online Interactive Teacher Talks In ELT: A Sociocultural and Interactionist Analysis - Nadira Syifa Azzahro; Setiarini Setiarini (CV. Rustam, 2025)
Education plays a pivotal role in shaping individuals by fostering cognitive, affective, and psychomotor growth while instilling values like character and morality. In English language teaching (ELT), teacher-student interaction is essential for developing linguistic and communicative competence. Frameworks such as socio-cultural theory and Communicative Language Teaching (CLT) emphasize meaningful dialogue, scaffolding within the Zone of Proximal Development (ZPD), and authentic communication. An observed Online ELT classroom interaction highlighted scaffolding techniques, error correction, vocabulary clarification, and conversational repair mechanisms. Using conversation analysis principles, the study identified evidence of scaffolding and features like turn-taking and negotiation of meaning. The findings revealed how interactive teacher talk fosters learner progression toward independent language use, aligning with Vygotsky’s mediation theory and the interactionist perspective. Repair strategies and dynamic turn-taking enhanced communicative competence, while CLT’s focus on real-world communication prepares learners for practical language application. These elements illustrate how linguistic input, feedback, and contextualized communication converge in teacher-student interactions, creating a dynamic process that supports language acquisition and prepares learners for authentic communication in real-world contexts.